Air Power Development Strategies for Safeguarding Airspace Sovereignty: A Systematic Review of Patterns and Typologies - Yanto S Manurung (Journal of Social Work and Science Education, 2026)
The strategic imperative of airspace sovereignty necessitates robust air power development, yet existing literature remains fragmented across technological, operational, diplomatic, and institutional silos, hindering a holistic understanding of effective strategic formulation. This study aims to synthesize thematic patterns and develop a comprehensive typology of air power development strategies through a systematic review of contemporary scholarship. Following the PRISMA 2020 guidelines, a systematic literature review was conducted on peer-reviewed journal articles indexed in the Scopus database and supplementary sources. After rigorous screening against predefined inclusion and exclusion criteria, 12 studies published between 2017 and 2025 were selected for thematic synthesis. The analysis reveals four dominant thematic patterns, capability-driven, technology-centric, diplomacy-oriented, and institutional governance factors, which are consolidated into four strategic typologies: capability-based, technology-focused, diplomacy-oriented, and hybrid strategies. The findings demonstrate a paradigmatic shift from siloed, platform-specific approaches toward integrated, multidimensional frameworks that combine military readiness, technological innovation, institutional strengthening, and international cooperation. Theoretically, this study bridges military innovation theory and the political economy of defense by offering a typological framework that clarifies strategic choices and enables cross-context comparative analysis. Practically, it provides policymakers with an adaptive roadmap for designing resilient air power strategies that balance capability modernization, technological adoption, and cooperative security to address contemporary airspace threats.